MicroRNAs (miRNAs) in the control of HF development and cycling: the next frontiers in hair research. Issue 11 (25th August 2015) - Andl, Thomas; Botchkareva, Natalia V.
Abstract: Hair follicle development and its postnatal regeneration are characterized by dramatic changes in its microanatomy and cellular activity, which are controlled by multiple signalling pathways, transcription factors and epigenetic regulators, including microRNAs (miRNAs). miRNAs and their targets form remarkably diverse regulatory networks, playing a key role in the execution of gene expression programmes in the different cell lineages of the hair follicle. This review summarizes the roles of miRNAs in the control of hair follicle development, cycling and hair pigmentation, emphasizes the remaining problems/unanswered questions, and provides future directions in this rapidly growing and exciting area of research.